Peptic Ulcer at the End of the 20th Century: Biological and Psychological Risk Factors - Susan Levenstein (Canadian Journal of Gastroenterology)
The prevailing concept of peptic ulcer etiology has swung over entirely in just a few years from the psychological to the infectious, yet the rich literature documenting an association between psychosocial factors and ulcer is not invalidated by the discovery of Helicobacter pylori. Physical and psychological stressors interact to induce ulcers in animal models, concrete life difficulties and subjective distress predict the development of ulcers in prospective cohorts, shared catastrophes such as war and earthquakes lead to surges in hospitalizations for complicated ulcers, and stress or anxiety can worsen ulcer course. Many known ulcer risk factors, including smoking, nonsteroidal anti-inflammatory drug use, heavy drinking, loss of sleep and skipping breakfast, can increase under stress; the association of low socioeconomic status with ulcer is also accounted for in part by psychosocial factors. Among possible physiological mechanisms, stress may induce gastric hypersecretion, reduce acid buffering in the stomach and the duodenum, impair gastroduodenal blood flow, and affect healing or inflammation through psychoneuroimmunological mechanisms. Psychosocial factors seem to be particularly prominent among idiopathic or complicated ulcers, but they are probably operative in run of the mill H pylori disease as well, either through additive effects or by facilitating the spread of the organism across the pylorus, while gastrointestinal damage by nonsteroidal anti-inflammatory drugs can also be potentiated by stress. Although the clinical importance of peptic ulcer is fading along with the millenium, due to secular trends and new therapies, it remains worthy of study as a splendid example of the biopsychosocial model.